Forensic podiatry : principles and methods - DiMaggio, John A.; Vernon, Denis Wesley; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2017)
Forensic Podiatry: Principles and Methods, Second Edition has been completely updated to reflect the latest developments and advancements in this changing field. New additions to the book, from the previous edition, include all new chapters on the expert witness, Frye Test, and Daubert Standard, as well as revised theories on gait analysis, bare footprint identification, and footwear examination. The new edition includes extensive case studies and an international compilation of current best practices.
part Section I: GENERAL FORENSIC CONCERNS -- chapter 1 The Crime Scene and Crime Laboratory -- chapter 2 Human Identification and General Principles and Definitions Relevant to Forensic Podiatry Practice -- part Section II: PODIATRIC FORENSIC CONCERNS -- chapter 3 Digital Photographic Techniques -- chapter 4 Bare Footprint Identification -- chapter 5 Footwear Examination and Analysis -- chapter 6 Forensic Gait Analysis -- chapter 7 IdentifiCation from Podiatry Records -- part Section III: MEDICAL LEGAL CONCERNS -- chapter 8 Expert Witness -- chapter 9 Standards of Practice, Governance, and Standard Operating Procedures -- chapter 10 Frye Test and Daubert Standard -- part Section IV: CASE READINGS -- chapter 11 Case Readings in Forensic Podiatry.
Keywords: Forensic podiatry; Forensic sciences; Footprints